The Utilization of Lactation Rooms by Health Workers in Medan City - Yani Sri Ningsih; Chrismis Novalinda Ginting; Sri Lestari Ramadhani Nasution; Mangatas Silaen; Putranto Manalu (Media Kesehatan Masyarakat Indonesia, 2022)
Exclusive breastfeeding for infants with working mothers still becomes a significant problem. The provision of on-site lactation rooms has not substantially impacted the utilization of lactation rooms. This study analyzes the factors that influence the utilization of breastfeeding rooms by health workers in all public health centers in Medan City. This study is a quantitative study using a cross-sectional design. The study involved 78 health workers who breastfed children under two years old. The determination of the sample used the total sampling technique. The results show knowledge (0.000), attitudes (0.002), practice (0.008), support from health workers (0.000), the availability of lactation rooms (0.000), and formula feeding (0.000) affect the utilization of breastfeeding rooms. The regression test results show that knowledge is the most influential factor in the utilization of the lactation room. Respondents with good knowledge have 9.477 times more opportunities to use the lactation room than respondents with poor knowledge. It can be concluded that the use of lactation rooms is influenced by factors such as knowledge, attitudes, practice, support from health workers, availability of lactation rooms, and formula feeding. It is recommended for local governments to provide adequate and comfortable facilities at each institution's offices to increase the utilization of breastfeeding rooms. The provision of a comfortable lactation room has implications for the mother's willingness to use the lactation room. However, it becomes difficult to realize without the support of colleagues.